Isolasi dan Karakterisasi Bakteri Pelarut Fosfat dari Rhizosfer Pisang Cavendish (Musa acuminata L.) - Putri, Jean Delliana; Sumardi, Sumardi; Farisi, Salman; Agustrina, Rochmah (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Phosphorus is a very important nutrient for plants. However, most of the phosphorus is bound by soil colloids and is insoluble, so the role of phosphate solubilizing bacteria is needed to release the bound phosphate. This study aims to isolate, characterize, and test the pathogenicity of phosphate solubilizing bacterial isolates. This research used an exploratory method including taking soil samples, bacterial isolation, calculating the density of bacterial colonies, calculating the phosphate solubility index value and selecting potential bacteria, morphological and physiological characterization, and pathogenicity test. The results showed that the colony density was 3,2 x 103 CFU/g with phosphate solubility index values ranging from 1,38-3,65. The colony with the highest phosphate solubility index value is JE1 with a value of 3,65; JE2 with a value of 3,63; JE3 with a value of 3,13; JE4 with a value of 3,08; and JE5 with a value of 2,94. Colonies have an irregular shape with undulate edges, the colony color is predominantly white with umbonate, raised and flat elevations. Most isolates have short bacillus cells that are Gram negative, do not form spores, are able to ferment glucose, produce the enzyme catalase, and are not motile. The pathogenicity test showed that only the JE1 isolate was not pathogenic to tobacco leaves.